Hyzine Flipbook as an Innovative Digital Learning Media for the Reproduction Module: An Effort to Improve Student Learning Achievement - Ahmar, Hamdiah; Andriany, Alia; Papendang , Harry Allan (ITScience (Information Technology and Science), 2024)
Advancements in education alongside technological developments have given rise to numerous innovations and creative solutions, making it easier for people to carry out their activities. This study aims to determine the effectiveness of using Hyzine Flipbook-based modules in improving student learning achievement in reproductive anatomy and physiology material. This study is a Research and Development (R&D) project aimed at developing instructional materials in the form of reproductive anatomy and physiology modules based on a flipbook format by adopting a development model. The development procedure follows the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. This manuscript focuses on the analysis phase, particularly regarding the characteristics of the students. Data analysis was conducted using univariate analysis techniques. The study was carried out over approximately five months, from July 2024 to December 2024. The sample consisted of 32 respondents, who were medical students selected using a purposive sampling method. The research instruments included various data collection methods such as questionnaires, interviews, observations, and evaluations tailored to each research variable. Data were collected by asking respondents to complete a questionnaire that reviewed the characteristics of the students. A total of 45% of students reported using digital media daily, while 50% reported using digital media several times a week.